2019
DOI: 10.1016/j.jneb.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of Program Evaluation Instruments for the iCook 4-H Curriculum

Abstract: Objective: To develop and test the validity of program outcome evaluation instruments for cooking, eating, and playing together for obesity prevention during iCook 4-H. Design: Instrument development for both youth and adults through pre-post testing of items newly constructed and compiled to address key curriculum constructs. Testing occurred throughout program intervention and dissemination to determine dimensionality, internal consistency and test-retest reliability, and validity. Setting: A 5-state out-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Finally, the reliability tests showed a wide range of Î coefficients or ICC coefficients, depending on the nature of the variables. These results are in line with other studies aimed at validating food and/or culinary skill questionnaires, although these studies analyzed the reliability of their tools using Spearman or Pearson correlation tests instead of the ICC test [18,19,22,24]. Overall, our results showed that the HCFQ has the ability to produce a similar score with the same participants under the same conditions over time and is therefore suitable for studying the effectiveness of cooking training interventions.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, the reliability tests showed a wide range of Î coefficients or ICC coefficients, depending on the nature of the variables. These results are in line with other studies aimed at validating food and/or culinary skill questionnaires, although these studies analyzed the reliability of their tools using Spearman or Pearson correlation tests instead of the ICC test [18,19,22,24]. Overall, our results showed that the HCFQ has the ability to produce a similar score with the same participants under the same conditions over time and is therefore suitable for studying the effectiveness of cooking training interventions.…”
Section: Discussionsupporting
confidence: 89%
“…Assessments at these time points included measuring children’s height, weight, waist circumference, and blood pressure as well as completing surveys. Survey questions assessed demographics, dietary intake, food security, cooking frequency, and cooking self-efficacy; program evaluation questions focused on cooking skills, family meals, physical activity, and goal setting [23-31]. We added questions after 12 months of the project to assess engagement with technological self-efficacy (ie, accessing the internet, and creating and uploading digital photos and videos to a study website).…”
Section: Methodsmentioning
confidence: 99%
“…Program leaders and assistants provided feedback to researchers about the curriculum through quick online process evaluations (Qualtrics, Qualtrics Labs Inc., Provo, UT; 2013) at the end of each session during the 4 phases of testing. 46,47 During the intervention pilot test and study, leaders were provided with participant process evaluation feedback so that they could make adjustments as needed; during the dissemination pilot test and study, leaders were provided with feedback upon request. The curriculum development team used leader feedback to address issues and questions.…”
Section: Journal Of Nutrition Education and Behavior Volume 51 Number 3s 2019mentioning
confidence: 99%
“…Throughout each study phase, the fidelity of curriculum implementation was assessed. Fidelity of implementation evaluations 46,47 were conducted to determine whether sessions were implemented as intended. After a model fidelity tool was investigated during the pilot test, sessionspecific tools were developed to gather attendance and the timing of sections, and to assess the engagement of participants and leader effectiveness.…”
Section: Journal Of Nutrition Education and Behavior Volume 51 Number 3s 2019mentioning
confidence: 99%